W JAKI SPOSÓB JĘZYK ANGIELSKI MOŻE UŁATWIĆ PROCES NAUKI JĘZYKA NIEMIECKIEGO NA POZIOMIE ZAAWANSOWANYM? (RAPORT Z BADAŃ WŁASNYCH) - Bawej, Izabela (Neofilolog, 2019)
The following article refers to the benefits and possible uses of English in the process of learning German. The author presents and explores the results of an inquiry conducted among students of Applied Linguis-tics at the Kazimierz Wielki University in Bydgoszcz who learn English as L1 and German as L2, which demonstrates their effective language learning strategies. The study shows conclusions drawn from the students’ answers and with examples shows that English can be a source for positive transfer to German.